2013
DOI: 10.4049/jimmunol.1300538
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Function of T Cells Infiltrating Visceral Metastases from Gastrointestinal Cancers and Melanoma: Implications for Adoptive Cell Transfer Therapy

Abstract: Adoptive cell transfer of tumor-infiltrating lymphocytes (TILs) can mediate cancer regression in patients with metastatic melanoma, but whether this approach can be applied to common epithelial malignancies remains unclear. In this study, we compared the phenotype and function of TILs derived from liver and lung metastases from patients with gastrointestinal (GI) cancers (n = 14) or melanoma (n = 42). Fewer CD3+ T cells were found to infiltrate GI compared with melanoma metastases, but the proportions of CD8+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 40 publications
6
76
0
Order By: Relevance
“…Therefore, TNF-neutralizing molecules might be useful in nonimmunocompromized patients affected with immunogenic melanoma. Interestingly, HLA-I expression was detected on more than 50% of melanoma cells in 69% of melanoma metastases (49). Evaluating HLA-I expression in melanoma biopsies would help define eligibility of patients for TNF blockade treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TNF-neutralizing molecules might be useful in nonimmunocompromized patients affected with immunogenic melanoma. Interestingly, HLA-I expression was detected on more than 50% of melanoma cells in 69% of melanoma metastases (49). Evaluating HLA-I expression in melanoma biopsies would help define eligibility of patients for TNF blockade treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports indicating that antitumor activity was detected in TIL samples of 81% of patients with metastatic melanoma [151], which was one of the best situations for generating tumor-reactive TILs. From patients with gastrointestinal (GI) cancers, however, less than 3% of expanded bulk TILs were tumor-reactive [162]. Thus, there is need to employ genetic methods to modify T cells to increase antitumor activities for adoptive cell therapy of cancer patients.…”
Section: Genetically Engineered T Cell Therapymentioning
confidence: 99%
“…Thus, adoptive cell transfer therapy with antitumor TILs may be extended to treat patients with other forms of cancers such as breast, renal, and lung cancers. Recent studies have shown that TILs generated from liver and lung metastases from patients with GI cancers had similar proportions of CD8 + T cells, T cell differentiation stage, expression of costimulatory molecules, and expansion scale for clinical application to those derived from patients with metastatic melanoma [162]. Different from TILs from metastatic melanoma, however, TILs from GI cancers usually did not maintain the antitumor activity after large-scale expansion and less than 3% of expanded bulk TILs from GI cancers were tumor-reactive.…”
Section: Prospects In Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that 4-1BB expression on tumor-infiltrating lymphocytes (TIL) can be used to identify tumor-reactive T cells (13,14), leading to the use of 4-1BB-selected TILs for adoptive cell therapy in a clinical trial for metastatic melanoma patients (NCT02111863). With regards to activation of the 4-1BB pathway, several preclinical studies have reported increased antitumor responses following treatment with an agonistic a-4-1BB mAb, primarily via CD8 þ T-cell activation (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%